Association of chemokine receptor gene variants with HIV‐1 genotype predicted tropism. Issue 10 (20th April 2014) - Parczewski, M; Urbańska, A; Maciejewska, K; Clark, J; Leszczyszyn‐Pynka, M
Abstract : Objectives: As a switch from chemokine (C‐C motif) receptor 5 [CCR5 (R5)] to chemokine (C‐X‐C motif) receptor 4 [CXCR4 (X4)] HIV‐1 tropism is associated with symptomatic and AIDS stages of infection, while chemokine receptor gene variants modify the tempo of HIV disease progression, we aimed to analyse the association between pretreatment HIV‐1 tropism and chemokine polymorphisms known to restrict disease progression. Methods: V3 genotype tropism prediction was performed in a group of 221 treatment‐naïve patients, with subsequent CCR5 Δ32 (rs333), CCR2 V64I (rs1799864), CCR5 promoter (−627 C/T; rs1799988) and CX3CR1 V249I (rs3732378) genotyping performed in 206 patients. Alleles with a protective effect were assigned positive values while risk alleles were assigned negative values to calculate genetic scores. χ 2 tests, Mann−Whitney U‐tests and logistic and linear regression models were used for statistical analyses. Results: R5 tropism was found in 85.5% of patients ( n  = 189) using a false positive rate (FPR) of 5.75% and in 72.8% of patients ( n  = 161) using an FPR of 10%. A higher frequency of the 5.75% FPR predicted R5 tropism was associated with the CX3CR1 A allele ( P  = 0.027). Lower additive genetic scores were associated with an increased frequency of 5.75% FPR predicted R5 tropism ( P  = 0.0059), with the trend confirmed by logistic regression [odds ratio (OR) 0.5819; 95% confidence interval (CI) 0.3457–0.9795; P  = 0.0416]. Viral load tended to increase with decreasing genetic score in the logistic regression analysis (slope = −0.127 ± 0.076; P  = 0.095; r 2  = 0.161). Conclusions: The CX3CR1 A allele and lower genetic scores may restrict the switch of HIV‐1 tropism from R5 to X4. This effect may be associated with the amount of co‐receptor on the cell surface. Chemokine receptor gene polymorphisms influence both disease progression and tropism variability.